Assessing The Factors Associated With Self-Management In Hypertension Patiens: Implementations For Healthcare Strategies - Jon Parulian Simarmata; Ballsy C. A. Pangkey; Sergio Yudi Midu; Bima Adi Saputra (Jurnal Keperawatan Profesional, 2026)
Hypertension is one of the most common diseases worldwide. Its treatment does not rely solely on medical therapy but also requires patients’ ability to perform effective self-management. This study aimed to identify factors associated with self-management among individuals with hypertension. A quantitative cross-sectional design was employed. Purposive sampling was used, resulting in 93 respondents based on G*Power calculations, including individuals with blood pressure ≥140/90 mmHg or <140/90 mmHg with a history of hypertension. Bivariate analysis was conducted using the chi-square test, while multivariate analysis used logistic regression. The results of the chi-square test showed significant relationships between self-management and duration of illness (p=0.011), level of knowledge (p=0.009), and social support (p=0.021). In contrast, age (p=0.218) and education level (p=0.346) were not significantly associated with self-management. Logistic regression analysis indicated that duration of illness (p=0.009; Exp(B)=4.467) and social support (p=0.006; Exp(B)=2.835) were significant factors influencing hypertension self-management. This study concludes that duration of illness, knowledge, and social support are related to hypertension self-management, whereas age and education are not. Community health workers are encouraged to involve families, social environment and develop structured self-management-focused health education programs. Further research using observational methods and additional variables is recommended.